The difficult path to a sustainable economic growth - Musu, Ignazio (Venice, 2017)
"Economic growth since the industrial era has reduced poverty and increased societies’ quality of life, but it also has implied negative environmental effects. There is an urgent need to correct this structural unbalance. The open issue is whether this correction implies sacrificing the perspective of economic growth or if it can be achieved by maintaining economic growth though changing its nature in a more environment oriented direction. In the following I argue that this second strategy is preferable and also more realistic, but it requires an appropriate combination of conditions and policies to be implemented. Environmental regulation, particularly through the use of appropriate price signals correcting negative environmental externalities, is necessary, but not sufficient to promote the required radical environment oriented innovations, particularly to build a low-carbon economy less and less dependent on fossil fuels. Environment oriented innovation policies are required, supported by a system of social norms and by a polycentric system of governance."